Pembentukan Nilai – Nilai Agama Dan Moral Di Kelompok A2 Studi Kasus Di Taman Kanak-Kanak Islam Terpadu Alkarimah - Sudarti Sudarti; Iin Maulina; Wilda firdianti (Jurnal Kajian Anak (J-Sanak), 2023)
Research objectives: planning, implementation and evaluation. This research uses qualitative research with case studies. Data collection methods were carried out through observation, interviews and documentation. The research subjects were 12 children from group A2 and 1 teacher. The findings stated that in planning the teacher prepared facilities and infrastructure using habituation learning methods, lectures, storytelling, singing and watching videos. The media used are storybooks, picture cards, and puzzles. The classical classroom arrangement is said to be sufficient because of the media, delivery of familiarization, knowledge and classroom arrangement. Implementation of morals and religion, educators get used to praying together, eating etiquette and affection. The name of Allah, ablution movements, through singing, and movements for the formation of children's morals and religion are said to be good. 11 children are developing because every day the teacher gives the child a view that there is good development in knowledge and behavior. At school, teachers every week hold tausiah and study the Koran. During the evaluation, educators review the activities carried out and make small notes on each development.